1987
DOI: 10.1002/j.1939-4640.1987.tb03318.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Appearance of Antisperm Autoantibodies in Lewis Rats Following Vasectomy

Abstract: An indirect enzyme-linked immunosorbent assay (ELISA) was employed to monitor antisperm autoantibodies in 16 Lewis rats for up to 36 weeks following vasectomy. This assay was capable of discriminating all prevasectomy from postvasectomy sera at a 1:16 dilution. Weekly serum samples were obtained for the first 13 weeks and bimonthly samples thereafter. Half of the animals developed a positive antisperm autoantibody response by the end of the first postoperative week. By the end of the second week, 81% of the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In this study, the immunobead assay we used did not detect significant levels of antisperm antibodies until after 15 days. Other studies have shown a response as early as 1 week after bilateral vasectomy in the Lewis rat model using the enzyme-linked immunosorbent assay method (Herr et al, 1987). It is unclear whether the cause for these differing results can be attributed to the experimental design (ie, unilateral vs bilateral vasectomy) or to the sensitivity of the assay method itself.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the immunobead assay we used did not detect significant levels of antisperm antibodies until after 15 days. Other studies have shown a response as early as 1 week after bilateral vasectomy in the Lewis rat model using the enzyme-linked immunosorbent assay method (Herr et al, 1987). It is unclear whether the cause for these differing results can be attributed to the experimental design (ie, unilateral vs bilateral vasectomy) or to the sensitivity of the assay method itself.…”
Section: Discussionmentioning
confidence: 99%